The Determinant of the Public Empowerment Toward the Prevention of Dangue Fever (DBD) in Uteun Geulinggang Village of North Aceh District - Rizauddin, Meurah M Lingga; Hidayat, Wisnu; Sembiring, Rinawati (Sari Mutiara Indonesia University Press, 2018)
Dengue hemorrhagic fever is a disease caused by dengue virus transmitted to humans by the bite of aedes aegypti mosquito. The province of Aceh has 21 regencies/ cities. Based on data from The Basic Health Research (Riskesdas) 2013 in Aceh province, down to date, DHF is a vector borne disease that is a priority in the program of controlling infectious diseases, both in Indonesia and in the world. In the past 12 months, clinical DHF can be detected in almost all districts/ cities in the province of Aceh (range of prevalence from 0.0 to 4.5%) (Riskesdas, 2013). This study aimed to determine the effect of community empowerment determinants on the prevention of dengue fever in the village of Uteun Geulinggang, North Aceh District to prevent the dengue fever. This study is an analytical study using Cross Sectional Analytical design with 57 heads of the family used as samples and the object of this study. The data was analyzed by using Bivariate and Univariate analysis. The results showed that there was no influence of public knowledge (p = 0.223), there was an influence of community attitudes (p = 0.003), there was an influence of information access (p = 0.000). It is recommended that health education can always guide the citizens and conduct health promotion to provide information about health to encourage people to live a healthier life and free from Aedes aegypti mosquitoes invasion so that there will be no more dengue hemorrhagic fever.